Організаційна структура системи матеріального забезпечення з метою інтеграції обліку з іншими функціями управління - Пугаченко, О. Б.; Puhachenko, O. (КНТУ, 2015)
У статті представлено напрямки удосконалення організаційної структури системи матеріального забезпечення, що сприяють посиленню взаємозв’язку обліку з іншими функціями управління. Запропоновано авторське бачення алгоритму вирішення основних завдань служби матеріального забезпечення у секторах закупівель, зберігання і руху та економічному секторі. The aim of the article is to develop the organizational structure of procurement system for the purpose of accounting integration with other functions of management. The following schemes have been developed in order to improve the organizational structure of the procurement system for the purpose of accounting integration with other functions of management: organization of compiling orders and specifications of material resources demand; activities related to ensuring the receipt of supplies; organization of the process related to providing industrial and economic activity by material resources for carrying out the production program; procedure of records management of material resources; organization of records management in the Purchases Unit; organization of the process related to placing, preparing for issue and issuing material resources to relevant subdivisions of the company; procedure of records management of material resources received in barns, their movements and issuing to subdivisions, and revealing the state of material resources; organization of operational control in the material resources storage and movement etc.
Organizational Structure of Procurement System for the Purpose of Accounting Integration with Other Functions of Management
Keywords: облік; функції управління; організаційна структура; матеріальне забезпечення; інтеграція; сектор закупівель; сектор зберігання та руху; економічний сектор; запаси; accounting; functions of management; organizational structure; procurement; integration; procurement unit; storage and movement unit; economic sector; stocks